2008
DOI: 10.1002/jbm.b.31296
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric particle formation through electrospraying at low atmospheric pressure

Abstract: Electrospraying is a simple and versatile technique capable of producing polymeric particles. However, most investigations carried out thus far have been performed at ambient atmospheric pressure without studying the influences of pressure on the formation of polymeric particles. Here, we report our investigation on the effects of varying the pressure and the solution concentration on the microstructures of electrosprayed polymeric particles. Pressures are varied from ambient atmospheric pressure to 380 mmHg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
3
19
0
1
Order By: Relevance
“…The spherical morphology was obtained only for high polymer concentrations (9 and 10 %w/v), while flattened morphology and coalescence between particles was observed for decreased polymer concentrations (5 and 7.5 %w/v) ( Figure 2). These results are in accordance with previous studies, where polymer concentration was often shown to be the most critical parameter in the morphology of electrosprayed particles [33]. …”
Section: Morphologysupporting
confidence: 93%
See 3 more Smart Citations
“…The spherical morphology was obtained only for high polymer concentrations (9 and 10 %w/v), while flattened morphology and coalescence between particles was observed for decreased polymer concentrations (5 and 7.5 %w/v) ( Figure 2). These results are in accordance with previous studies, where polymer concentration was often shown to be the most critical parameter in the morphology of electrosprayed particles [33]. …”
Section: Morphologysupporting
confidence: 93%
“…Chloroform has a much lower boiling point of 61.2 °C, explaining the textured surface that was observed. Such texture was also seen in an even more pronounced way when electrospraying PCL with dichloromethane [33], which boils at 40 °C, corroborating this theory. In the case of in vivo implantation, it is noted that the topographical complexity of a biomaterial is preferred for cell attachment since it generates an increased number of anchoring sites for cells [38].…”
Section: Morphologysupporting
confidence: 74%
See 2 more Smart Citations
“…Our results were consistent with previous findings, such that the polymer concentration was the most pivotal factor determining the topography of particles. 32) Decreasing the flow rate produced particles with more widely dispersed size ranges. High flow rate resulted in particles with somewhat uniform size distribution; however, a few fibers were observed.…”
Section: Resultsmentioning
confidence: 99%